Relacje modalne we współczesnych aktach normatywnych - Łapa, Romana (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2014)
The author examines the language of the law. She refers to the contemporary acts; the legal regulations are the subject of her description. The author analyses legal cases which have been interpreted on the basis of the regulations. She discusses a modal dimension of the relationships which create legal cases and also makes closer characteristics of the participants of actions who are connected with these relationships. Language exponents of individual relations are presented. In order to emphasise specific character of legal material, the author precedes each description by indicating the peculiarities of modal dependence which are visible in sentences containing the so-called basic modal units. These sentences stem from other than legal modern Polish texts.